(untitled) (Journal of the College of Basic Education, 2022)
ZnO Polycrystalline films were prepared on glass substrate by solvent evaporation at 25°C, and post annealed in air at range of annealing temperatures of (100, 200,300°C) for 1 hour. The samples were characterized by analyzing the structural and optical properties. X-Ray diffraction results